Business process modelling using discrete-event simulation: current opportunities and future challenges. (2nd June 2005) - Hlupic, Vlatka; De Vreede, Gert-Jan
Competitive pressures and global business trends urge many organisations to radically change business processes. Although this can provide significant benefits such as reducing costs or improving efficiency, there are substantial risks associated with it. Using simulation for modelling and analysis of business processes can reduce that risk and increase the chance for success of business process reengineering projects. This paper investigates the potential of simulation to be used for business process modelling and discusses its main challenges and opportunities. Following a discussion on business process modelling methods and tools, the use of simulation modelling for evaluating alternative business process arrangements is investigated. Two examples of simulation models representing business processes are presented and discussed. Future trends and challenges in business process simulation are discussed and conclusions are drawn.